Impact of energy storage industry development on the low-carbon economy: evidence from China - Chen, Jian; Li, Hanzun (Frontiers in Energy Research, 2024)
Introduction: Facing the problem that it is difficult to reconcile development and carbon reduction in the energy sector, this study explores the impact mechanism of the development of energy storage industry on low-carbon economy from the perspective of the energy trilemma. Methods: Using a moderated two-mediation model and data from 275 cities in China, this study explores the differences in the impact mechanisms of the development of the energy storage industry on the low-carbon economy in different regions of China. Results: This study draws the following conclusions: first, the development of the energy storage industry can promote the green economy by facilitating technical support and the development of new energy industries. Second, financial support can regulate the effect of this mediating role. Third, in China, the contribution of energy storage industry development to green development is significantly higher in the northern region than in the southern region due to the differences in impact mechanisms. Discussion: The results of this study provide an effective path for developing countries to balance energy sector development, security, and low-carbon.